الشواهد الحديثية في جمع الجوامع للسيوطي: دراسة وصفية تحليلية - فارس، إبراهيم عبدالعزيز حسين; حماد، أسامة خالد محمد (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2022)
تناول هذا البحث آراء عالم نحوي موسوعي، وهو الإمام السيوطي، وعرض لجهوده النحوية التي قامت على السماع، وعني بجمع الشواهد اللغوية التي استشهد بها السيوطي من أحاديث النبي صلى الله عليه وسلم. ودراستها وفق قواعد الاستشهاد وأصوله، وقد جاء البحث متضمنا لتمهيد ومبحثين، بدأ بمقدمة بينت مكانة السيوطي الكبيرة عبر مؤلفاته المتعددة، وأهمية مصنفاته النحوية التي تفرد بها، وقد اعتمد الباحثان المنهج الوصفي التحليلي فتناول المبحث الأول التعريفات بالسيوطي، وعلم الحديث، ومواقف النحاة من الاستشهاد به، ثم بينا في المبحث الثاني كيفية تناول السيوطي لهذه الأحاديث في كتابه جمع الجوامع، وكيف اتخذها سبيلا للاستدلال على صحة القاعدة اللغوية، ومن أهم المسائل التي تناولها: إن المخففة، تقدير الفاعل، تقدير متعلق الجار والمجرور في البسملة، جواز ما جاز في الضرورة في النثر، خواص الاسم، ثم خرجا بمجموعة نتائج وتوصيات، فكان من أهم النتائج: تميز الإمام السيوطي بالاستشهاد بالحديث الشريف واتخاذه له مادة للاستدلال النحوي واللغوي، وهو بهذا أزال الحرج الذي وضعه النحاة الأوائل حول ذلك، وبالرغم من ميل السيوطي إلى مدرسة البصرة إلا أنه كان يخالفهم في الاستدلال والتأويل، فيجيز ما يجيزه أعلام مدرسة الكوفة. This research addressed an encyclopedic grammatical scholar, Al-Imam Al-Suyuti, and presented his grammatical efforts that were based on listening. This research is highly concerned with collecting linguistic evidences that Al-Suyuti cited from the hadiths of the Prophet (peace be up on him), and studying them according to the rules and principles of citation. The research included an introduction and two chapters. The introduction explained the high rank of Al- suyuti through his various books and his unique grammatical works. The researchers adopted the descriptive analytical approach. The first chapter dealt with presenting Al-Suyuti, the science of hadith and the grammarians’ attitudes towards his citation. The second chapter explained how Al-Suyuti dealt with these hadiths in his book (jame aljawamie) and how he used them as a way to infer the validity of the linguistic rule. The most important issues are: ('in almukhafafa, tqdyr alfael, tqdyr mtelq aljar wal mjrwr fi albasmla, jwaz ma jaz fi aldrwrt fi alnthri, khwass aliasm) The researchers came out with set of results and recommendations, the most important results are: Imam al-Suyuti distinguished himself by citing the honorable hadith and using it as a material for grammatical and linguistic evidences, as a result he removed the suspicion and embarrassment of making a mistake by the early grammarians and despite al-Suyuti’s inclination to Al- Basra school, he disagrees them in inference and interpretation, so he admits what Al-kufa scholars would admit.
Keywords: النحو العربي -- السيوطي، جلال الدين عبدالرحمن، ت. 911 هـ. -- الشواهد اللغوية -- الأحاديث النبوية